Pengaruh Penggunaan Media Audiovisual Berbasis Digital Terhadap Keterampilan Literasi Membaca Permulaan Di Kelas 2 Min 6 Aceh Utara - Suci Aulia Safira; Nisa Mawaddah; Syibbra Malasi; Selvi Saprina; Samsul Bahri (Pencerah, 2025)
This study aims to examine the effect of using digital audiovisual media on the literacy skills and early reading abilities of second-grade students at MIN 6 Aceh Utara. This study uses a quantitative approach with a pre-experimental design involving one experimental class. The research instrument is an oral test administered in the form of a pre-test and post-test. The total sampling for this study was 10 second-grade students at MIN 6 Aceh Utara. Data analysis in this study used a parametric test, namely a dependent difference test (t-test). The results showed a significant effect from the dependent t-test results, namely 7.927, which was greater than 1.883 in the students' early reading skills. The average pre-test score was 57, which is categorized as very low. After being given treatment with digital audiovisual media, the average post-test score increased to 89.5, which is categorized as very high. This increase proves that the use of audiovisual media can effectively improve students' early reading literacy skills.